Phenol degradation on heterogeneous catalytic oxidation by using cobalt-natural zeolite catalyst - Syaifullah Muhammad; Edy Saputra; Shaobin Wang; Moses O. Tadé (Syiah Kuala University, 2011)
Two types of catalysts based on Indonesia Natural Zeolite (INZ) and Australia Natural Zeolite (ANZ) were prepared by impregnation of 5 % of active metal cobalt. The synthesized catalysts were calcined in air at 5500C for 6 hours. The catalysts were then used to degrade phenol concentration in heterogeneous catalytic oxidation with the presence of oxone as peroxymonosulphate source. The catalysts were also characterized by several techniques such as SEM, EDS and N2 adsorption. It was found that Co-INZ and Co-ANZ are effective catalyst in activation of peroxymonosulphate to produce sulphate radicals to degrade phenol concentration. In reaction test of 5 hours, with condition of 25 ppm phenol, 0.2 g catalyst loading, 1 gram oxone, 250C and stirring speed of 400 rpm, Co-INZ and Co-ANZ could reduce phenol up to 100% and 70% respectively. Further, several parameters such as amount of catalyst loading, phenol concentration, oxidant concentration and temperature are found as key factors in phenol degradation. Moreover, based on the trend of phenol degradation following by kinetic study, it was proved that the pseudo first order kinetics would fit to phenol oxidation with the rate constants of 0.0106 and for 0.0033 Co-INZ and Co-ANZ respevtively